2012
DOI: 10.14417/ap.439
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento parental de mães adolescentes

Abstract: O objectivo é o de construir um modelo teórico sobre o comportamento parental de mães adolescentes. O estudo teve a participação de 21 mulheres que foram mães na sua adolescência, com idades compreendidas entre os 14 e os 18 anos na altura do parto e de uma psicóloga que trabalha com mães adolescentes. Na altura das entrevistas as mães tinham idades compreendidas entre os 15 e os 35 anos de idade. Foram analisadas 22 entrevistas das quais 17 pertencem a estudos anteriores (Bentes, 1996; Araújo, 2000; Alves, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
14

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
(6 reference statements)
0
3
0
14
Order By: Relevance
“…It is known that adequate guidance for young women can prevent pregnancy. 34 The absence of dialogue, acceptance, and understanding make young women vulnerable, with several undesirable consequences, including an early and unwanted pregnancy. 35 In addition, pregnancy imposes risks to adolescents, who are still physically and psychologically immature, increasing the risk of gestational complications, lack of prenatal care, and absence of social support networks.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that adequate guidance for young women can prevent pregnancy. 34 The absence of dialogue, acceptance, and understanding make young women vulnerable, with several undesirable consequences, including an early and unwanted pregnancy. 35 In addition, pregnancy imposes risks to adolescents, who are still physically and psychologically immature, increasing the risk of gestational complications, lack of prenatal care, and absence of social support networks.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of adolescent mothers reported the presence of family support in the execution of household chores and care of themselves and their child. This can be fundamental, because many young people feel unprepared to care for a child at this time of life, with the aggravating factor of financial instability further contributing to feelings of fear and insecurity (11) . Evidence suggested that changes occurred for better or much better in the relationship between the young mother and her family after the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is believed that the positive interaction between the young mother and her family, as well as with the father of her child, facilitates the availability for support in their role as a mother, and in the provision of child care. This condition is indespensible for the mother to feel supported, and the neonate may develop in a calm and welcoming environment; this also encourages a better relationship within the mother-child dyad (11) . Therefore, considering the importance of favorable relationships between the adolescent mother and the individuals belonging in her daily life, this research had as its objective to analyze the perception of adolescents about family and marital relationships after pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Tais características mostram desde maturidade no exercício do papel materno (como visto em Carolina), como algum despreparo (observado em Júlia e Fabiana), frequentemente mencionado na literatura sobre a maternidade na adolescência (BIGRAS, PAQUETTE, 2007;CARLOS et al, 2007;FIGUEIREDO, 2000FIGUEIREDO, , 2001.…”
Section: Discussão Geral E Considerações Finaisunclassified
“…As investigações sobre a maternidade nessa faixa etária, em geral, têm como foco os aspectos desenvolvimentistas e psicossociais (BRAN-DÃO, HEILBORN, 2006;CARLOS et al, 2007;DIAS, AQUINO, 2006;ESTE-VES, MENANDRO, 2005;FIGUEIREDO, 2000FIGUEIREDO, , 2001HOGA, 2008;KRISTEN, MONTGOMERY, 2004) e demonstram que as mães adolescentes, além de lidarem com os desafios impostos pelo contexto de maternidade, também se confrontam com os desafios próprios de sua etapa de desenvolvimento (CARLOS et al, 2007).…”
Section: Introductionunclassified